2017
DOI: 10.1186/s13411-017-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of assay for determining β-glucosidase activity in human saliva

Abstract: Background: β-glucosidase is an enzyme important to flavour enhancement. It hydrolyzes glucosides to release aglycones-aroma precursors that are bound to a sugar molecule-thereby making them available to contribute to the flavour of foods and beverages. While there is strong interest within the food and beverage industry to optimizing flavour through the use of exogenous and endogenous glucosidase in production, little is known regarding the possible occurrence of these enzymes within the human oral cavity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Further, the limit of detection and Stern–Volmer quenching constant were also calculated from the Stern–Volmer plot (Figure c) as 134 nM and 2.23 × 10 5 , respectively. Very few reports are available for the detection of β-glucosidase. Compared to those reports, our method is simple, reliable, inexpensive, and sensitive.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, the limit of detection and Stern–Volmer quenching constant were also calculated from the Stern–Volmer plot (Figure c) as 134 nM and 2.23 × 10 5 , respectively. Very few reports are available for the detection of β-glucosidase. Compared to those reports, our method is simple, reliable, inexpensive, and sensitive.…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, β-glucosidase has another essential role in the isolation of bacteria and the detection of o -hydroxycinnamic acid in Melilotus alba leaves . A few reports are available for detection of β-glucosidase using polyacrylamide gel electrophoresis, spectrophotometric assay, fluorescence, and colorimetry techniques. Among them, the fluorescence-based approach was invented to quantify biomolecules owing to its high sensitivity, ease of usage, simple system integration, and cost-efficiency. Many fluorescent probes such as organic/inorganic molecules/complex, dyes, noble metal clusters, and quantum dots are used in analytical chemistry for the detection of a variety of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together all these facts along with the recent reported detection of β-glucosidase activity in human saliva [ 23 , 24 ] we investigated here the correlation between β-glucosidase activity and the occurrence of halitosis. In our hypothesis, increased salivary β-glucosidase activity is directly involved in the hydrolysis of glycosidic substrates from human saliva, which can alter the volatile profile leading to the occurrence of halitosis.…”
Section: Introductionmentioning
confidence: 77%
“…Stradwick et al confirmed β-glucosidase activity in the supernatant of human saliva after centrifugation. The activity was detected in 19 out of the 20 tested patients, but no correlation with clinical data was performed and the authors suggest that individual taste perception and food preference may be associated with β-glucosidase activity in saliva [ 23 ]. Our data showed no β-glucosidase activity in saliva supernatant after centrifugation, in agreement with other studies [ 18 ] however, enzymatic activity was observed in the salivary pellet after centrifugation and in whole saliva samples, suggesting that these enzymes are produced by oral bacteria,.…”
Section: Discussionmentioning
confidence: 99%
“…In saliva, a bacterial origin of glycosidase activity has been suggested, although it is significant only after several days of reaction (Muñoz-González et al, 2015), raising questions regarding their contribution to the perception of a food during the time of its consumption. The existence of human glycosidase activity in saliva (Stradwick et al, 2017) and the oral epithelium (Mallery et al, 2011;Walle et al, 2005) should also be further investigated. This activity is believed to come from human beta-glucosidase (encoded by GBA3), which is present in the mouth (Ghosh et al, 2012) and is known to participate in the in vivo metabolism of certain glycosylated derivatives (Nemeth et al, 2003).…”
Section: Glycoside Conjugatesmentioning
confidence: 99%